Relationship between organizational commitment and citizenship behaviors of personnel in subdistrict administrative organizations in Samphran District, Nakhon Pathom Province. - Kirin, Panatda (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aimed to 1) study levels of organizational commitment and citizenship behaviors of personnel in subdistrict administrative organizations in Samphran District, Nakhon Pathom Province; 2) compare level of organizational citizenship behaviors of personnel as classified by personal factors; and 3) study relationship between organizational commitment and citizenship behaviors. The research instrument was a questionnaire. The sample was 234 personnel and the statistics used for data analysis were percentage, mean, standard deviation, t-test, one way ANOVA and correlation coefficient. The research results were: 1) Overall the level of organizational commitment of personnel was at a high level. They were, in the descending order, affective commitment, continuous commitment and normative commitment. The overall level of organizational citizenship behaviors was also at a high level. The priorities were the aspect of considerate behaviors to prevent work-related problem, voluntary actions to help others, willing to work beyond minimal requirement, willingness to tolerate the inevitable inconveniences, and voluntary participation in organizational functions. 2) There was no difference in the level of organizational citizenship behaviors among the personnel who differed in sex, age, education, monthly income and work position. However, those with difference in work tenure had the different level in organizational citizenship behaviors with the statistically significant level of .05. 3) All aspects of organizational commitment related with organizational citizenship behaviors. When considering each aspect, the aspects of affective commitment, continuous commitment and normative commitment related with organizational citizenship behaviors with statistically significant level of .05. Article history : Accepted 16 August 2014 SIMILARITY INDEX = 2.72